2000
DOI: 10.1139/cjpp-78-5-367
|View full text |Cite
|
Sign up to set email alerts
|

Fenofibrate lowers blood pressure in two genetic models of hypertension

Abstract: Fenofibrate, a commonly used lipid lowering drug, induces the expression of the gene coding for cytochrome P450-4A, whose major product is 20-hydroxyeicosatetraenoic acid (20-HETE). 20-HETE, a potassium channel antagonist, could increase or decrease blood pressure (BP). We studied the effects of four weeks of oral fenofibrate on BP, urine output (UVol), plasma renin activity (PRA), and urine protein excretion in young (4-5 weeks) stroke prone spontaneously hypertensive rats (SHRSP), older (25 weeks) SHRSP, Dah… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
25
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 18 publications
7
25
0
Order By: Relevance
“…Indeed, there is evidence that nitric oxide (24) and carbon monoxide (1,3) that is present in the outer medulla binds to the heme of CYP4A proteins and inhibits the formation of 20-HETE. Nonetheless, our finding that increasing the renal formation of 20-HETE in this case by transfer of chromosome 5 reduces salt sensitivity of blood pressure in SS.5 BN rats is consistent with previous data, indicating that induction of the synthesis of 20-HETE in the kidney with fibrates opposes the development of hypertension in SS rats and other models of hypertension (30,33,43). In contrast, the increase in 20-HETE formation in renal microvessels in the SS.5 BN strain would be expected to increase vascular tone and promote the development of hypertension.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, there is evidence that nitric oxide (24) and carbon monoxide (1,3) that is present in the outer medulla binds to the heme of CYP4A proteins and inhibits the formation of 20-HETE. Nonetheless, our finding that increasing the renal formation of 20-HETE in this case by transfer of chromosome 5 reduces salt sensitivity of blood pressure in SS.5 BN rats is consistent with previous data, indicating that induction of the synthesis of 20-HETE in the kidney with fibrates opposes the development of hypertension in SS rats and other models of hypertension (30,33,43). In contrast, the increase in 20-HETE formation in renal microvessels in the SS.5 BN strain would be expected to increase vascular tone and promote the development of hypertension.…”
Section: Discussionsupporting
confidence: 82%
“…Further studies have indicated that induction of renal P4504A activity with clofibrate improves the pressure natriuresis relationship in Dahl S rats by primarily increasing GFR [29,30]. These contradictory results remain to be explained, and may, in fact, reflect the differences among various animal models [31].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the effect of fenofibrate to reverse the elevated blood pressure response to angiotensin II infusion is accompanied by decreased oxidative stress and inflammation in the vascular wall (11). PPAR␣ expression is increased in blood vessels of spontaneously hypertensive rats (22), and fenofibrate lowers blood pressure in these rats (11,23). Fenofibrate also prevents cardiac fibrosis in mineralocorticoid-dependent hypertensive rats (24).…”
Section: Effects Of Therapies On Adiponectin and Insulin Resistancementioning
confidence: 99%